Metode Ijtihad Kontemporer Versi Yusuf Qordhawi - Rini Angreni Hasibuan; Azharia Khalida; Efendi; Zaim Rais (Kariman: Jurnal Pendidikan Keislaman, 2023)
This article is motivated by the emergence of various problems at this time, but did not exist in ancient times. So it is very necessary for the ijtihad of the scholars to re-establish a law. Yusuf al-qordhawi as a contemporary scholar has his own way of establishing laws on contemporary issues. In that regard, this article aims to describe the contemporary ijtihad method used by Yusuf al-qordhawi in establishing a law. This research is a descriptive qualitative research using literature review. Data sources in this study are books, journals and other things related to the problem. This research is carried out systematically, namely collecting data, processing, concluding and using certain techniques to find answers to problems. The results showed that Al- Qardhawi was very selective and rational in establishing laws on the problems at hand. Here are some fatwas set by yuusf qordhawi with his ijtihad, namely about the legal determination of shaking hands between men and women who are not mahram, the determination about being allowed to breastfeed through the Breast milk Bank (Breast Milk), and not prohibiting marriage between milk mothers and relatives, Determination about the obligation of a father to ask for the consent of his daughter to be married, and must not force him to marry,  Against al-Qaradhawi's fatwa on abortion due to rape that occurred in Bosnia. Yusuf qordhawi has several ijtihad methods, namely ijtihad intiqho'I, ijtihad insya'I and ijtihad combined insha'i and intiqho'i. and also still requires the postulates of the establishment of law in classical times, such as ijma, qiyas, istihsan, and others. And the main thing is that the legal establishment remains sourced from the Quran and hadith.